Severe Acute Respiratory Syndrome Coronavirus 2 Spike Protein Based Novel Epitopes Induce Potent Immune Responses in vivo and Inhibit Viral Replication in vitro - Vishwakarma, Preeti; Yadav, Naveen; Rizvi, Zaigham Abbas; Khan, Naseem Ahmed; Chiranjivi, Adarsh Kumar; Mani, Shailendra; Bansal, Manish; Dwivedi, Prabhanjan; Shrivastava, Tripti; Kumar, Rajesh; Awasthi, Amit; Ahmed, Shubbir; et al. (Frontiers in Immunology, 2021)
SARS-CoV2 virus initiates infection by attachment of the surface exposed spike glycoprotein to the host cell receptors. The spike glycoprotein (S) is the promising target for inducing immune responses and providing protection, thus the ongoing efforts for the SARS-CoV2 vaccine and therapeutic developments are mostly spiralling around S glycoprotein. The matured functional spike glycoprotein is presented on the virion surface as trimers, containing two subunits S1 (virus attachment) and S2 (virus fusion). The S1 subunit harbours the N-terminal domain (NTD) and the receptor-binding domain (RBD). The RBD is responsible for binding to host cellular receptor angiotensin-converting enzyme 2 (ACE2). The NTD, RBD of S1, and the S2 of S glycoprotein are the major structural moieties to design and develop spike-based vaccine candidates and therapeutics. Here, we have identified three novel epitopes (20-amino acid peptides) in the regions NTD, RBD, and S2 domains respectively, by structural and immunoinformatic analysis. We have shown as a proof of principle in the murine model the potential role of these novel epitopes in inducing humoral and cellular immune responses. Further analysis has shown that RBD and S2 directed epitopes were able to efficiently inhibit the replication of SARS-CoV2 wild type virus in vitro suggesting their role as virus entry inhibitors. Structural analysis revealed that S2-epitope is a part of the heptad repeat (HR2) domain, which might have plausible inhibitory effects on virus fusion. Taken together, this study discovered novel epitopes that might have important implications in the development of potential SARS-CoV2 spike-based vaccine and therapeutics.